Construcción de un modelo musculo-esquelético desarrollado en opensim para la parametrización cinemática de la marcha en personas con amputación transfemoral (2021)
The gait analysis is an important diagnostic tool for the assessment of pathologies or traumatic injuries and for the control and follow-up of an osteomuscular alteration. With it, biomechanical variables, both kinetic and kinematic, are evaluated, these can be evaluated experimentally or by means of musculoskeletal models that simulate the behavior of the body. In this work, a transfemoral prosthesis was created from SolidWorks which was exported in . STL format and adapted to be included in a model developed in OpenSim that allows quantification of kinematic gait variables. The validation was performed virtually, due to the health emergency caused by COVID-19, using an open-access database that contains kinematic data on the gait of patients with transfemoral amputation. The main results obtained in this work are: a functional model in OpenSim that allows to quantify kinematic variables such as cadence and stability, as well as, by comparing the graphs obtained in Matlab and OpenSim, to determine that there is a lag during the support between normal and prosthetic gait, which for knee extension is ±5° and, as for hip extension, hyperextension exceeding 30° on the amputated side is evident. It was concluded that adaptive processes are of great importance, since the shorter the time with the prosthesis, the speed of walking that can be tolerated by the amputee is lower and the rigidity is much greater